La diferencia desconectada. reflexiones sobre identidad y diferencia en la sociedad de la información - Guiomar, Salvat Martinrey; Vicente, Serrano Marín (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The article examines some effects of information and communication technologies (ICT) have on old categories such as identity, difference, community, society or alienation. Under the term paradox of difference attempts to uncover the basic mechanism by which the multiplication of differences is built from a new instance both material and virtual